DETEKSI SARS COV-2 DENGAN METODE REVERSE TRANSCRIPTION LOOP MEDIATED ISOTHERMAL AMPLIFICATION (RT-LAMP) TINJAUAN NARRATIVE REVIEW - Muhammad Rizky Wibowo (2021)
The new type of virus that has never been previously identified in humans by WHO is named SARS CoV-2 and the name of the disease is Covid-19. This virus has spread throughout the world very quickly. Due to its very rapid spread, it demands a Point of Care Test (POCT) detection test that is fast, simple, cost-effective and accurate for diagnosis. The main WHO diagnostic standard used worldwide is the RT-PCR method. This method can detect the presence of viral genetic material in the human body with accurate results. However, it has many limitations, namely sophisticated laboratory requirements, the need for skilled laboratory personnel, the use of complex protocols, long waiting times and expensive testing costs to obtain results. The researchers made efforts to find an alternative detection, namely the LAMP method. LAMP is a fast, simple and sensitive method of RNA detection carried out under isothermal conditions. This method can be carried out using a very simple device, it can even be powered by a battery, so that it can be taken to the field or close to the patient. This method can diagnose the virus quickly, inexpensively and does not require skilled laboratory personnel. The RT-LAMP assay for the diagnosis of SARS CoV-2 can yield a sensitivity comparable to that of standard RT-PCR. This method is more suitable for diagnosis in places where health facilities are inadequate, such as in rural areas in developing countries.